Direct Oral Anticoagulants in Select Patients With Hypercoagulable Disorders. Issue 7 (July 2021) - Valanejad, Sara M.; Davis, Kyle A.
Objective: To summarize the literature assessing the safety and efficacy of direct oral anticoagulants (DOACs) for the acute treatment and secondary prevention of venous thromboembolism (VTE) in select patients with hypercoagulable disorders. Data Sources: An electronic PubMed literature search was conducted from January 2010 to July 2020 using the following keywords: DOAC, rivaroxaban, apixaban, dabigatran, edoxaban, thrombophilia, cancer, antiphospholipid syndrome, protein C deficiency, protein S deficiency, antithrombin deficiency, factor V Leiden, prothrombin G20210A gene mutation, congenital thrombophilia, hypercoagulable, hereditary thrombophilia, acquired thrombophilia . Study Selection and Data Extraction: Articles were included if they reported clinical outcomes associated with cancer-associated VTE, antiphospholipid syndrome (APS), and other hereditary thrombophilias. Data Synthesis: The safety and efficacy of using a DOAC is highly dependent on the type of hypercoagulable disease state. Current trials support the use of edoxaban, rivaroxaban, and apixaban for the treatment of cancer-associated thrombosis (CAT), with apixaban being preferred because of lower bleeding rates compared with standard of care. The use of DOACs, especially rivaroxaban, have been associated with worse outcomes in patients with APS, whereas data on DOAC use in hereditary thrombophilia remains scarce and limited to low-risk patients. Relevance to Patient Care and Clinical Practice: This review evaluates the literature assessing the safety and efficacy of DOACs in patients with various hypercoagulable disorders. Conclusions: The current body of evidence supports the use of select DOACs for the treatment of CAT. In contrast, DOAC use in patients with APS and hereditary thrombophilia should be avoided at this time.